Profile of H1N1 infection in a tertiary care center - Srinivasa Raghu Jagannatha Rao; Malini Jagannatha Rao; Nandini Swamy; B L Umapathy (Wolters Kluwer Medknow Publications, 2011)
Background: A novel swine origin influenza virus (H1N1) is spreading worldwide and threatens to become pandemic.H1N1 critical illness mostly affects young patients and is often fatal. Aim: The aim of the present study is to evaluate the clinical characteristic of H1N1 infection in a tertiary care hospital. Materials and Methods: A total of 92 nasal and pharyngeal swabs from suspected cases of swine flu were processed by real time reverse transcriptase polymerase chain reaction (rRT-PCR). Result: Twenty(21.73%) were positive of which two were treating physicians and five (25%) patients expired. Conclusions: The age group of positive cases of H1N1 was between 21 and 30 years and age group of patients who died ranged from 40 to 45 year. This overview indicates that although the majority of hospitalized persons infected with novel influenza A (H1N1) recovered without complications, certain patients had severe and prolonged disease. It was also noted that 2009 influenza A (H1N1) infection - related clinical illness predominantly affects young patients. All hospitalized patients with novel influenza A (H1N1) infection should be monitored carefully and treated with antiviral therapy. Mandatory vaccination of health-care workers is especially important in emerging pandemic.